Du Crime À La Chose, Une Scénographie De L’indicible Chez Maupassant (International Journal of Scientific Research and Management (IJSRM), 2024)
This study concerns a study devoted to the staging of the crime by Maupassant. By focusing on the evocation of the “thing”, we brought out the scenography of the unspeakable in some short stories by Guy de Maupassant. The short story writer evokes incest, adultery or fornication using the word “thing”. Thus the thing is considered as that which is concealed. The “thing” in certain Maupassantian short stories means the unspeakable which is either incest, adultery or fornication. It also designates death, crime or anything that the writer chooses not to name. The “thing” is also described as “infamous” when what the short story writer designates is detestable, ignoble and shameful. It is this repugnance of what is mentioned that pushes the writer to use the term “thing”.